THE ANALYSIS OF SATISFACTION OF STUDENTS IN THE CHRISTIAN UNIVERSITY OF INDONESIA TOWARD ACADEMIC INFORMATION SYSTEM (AIS) SERVICE: (Case Study Of Students In The Christian University Of Indonesia) - Hutajulu, Oktafia Agrethia; Tobing, Fenny BNL (Fundamental Management Journal, 2019)
In the research analysis of satisfaction of students in the christian university of indonesia toward academic information system (ais) service, using a research model that is "Importance and Performance Analysis", using 'Likert' to measure the research variables. The results showed that Indonesian Christian University students were satisfied with the Academic Information System (AIS) service. The attributes that give satisfaction are as follows: AIS information is always updated, AIS provides a menu of academic consultations between students and lecturers of Academic Advisor (PA), AIS provides financial information to find out the number of college bills, AIS displays information about student academic activities and AIS makes it easy for students to the process of making a study plan. Suggestions for Academic Information Systems (AIS) Indonesian Christian University is that AIS looks more communicative, provides more academic information, and displays more accurate data in accordance with the wishes of students. Key words: Customer satisfaction, The importance and performance analysis, Academic Information System.